Selecting outcome measures to validate prognostic biomarkers of paediatric mild traumatic brain injury: challenges and priorities - Attwood, Jonathan E.; Lövgren, Izabelle; Forsyth, Rob; Demarchi, Célia; Thayanandan, Tony; Prisco, Lara; Ganau, Mario; Roberts, Rebecca; Scarff, Kate; Newton, Julia L.; DeLuca, Gabriele C.; Lawrence, Tim (Frontiers in Neurology, 2025)
Outcomes following paediatric mild traumatic brain injury (mTBI) are extremely heterogenous. While emerging biomarkers promise enhanced prognostic accuracy, a critical question remains unanswered—which outcome measures provide the most accurate assessment of injury impact? In this article, we highlight barriers to selecting appropriate outcome measures, including variability in how outcomes are defined and the wide range of assessment tools used. With reference to the most recent literature, we summarise current evidence of adverse outcomes following paediatric mTBI and highlight emerging candidate biomarkers of these outcomes. We emphasise the unique challenges associated with interpreting outcome measures in younger patients, from the impact of developmental stage and assessment timing to the influence of injury-independent factors. We assert the need to consider these obstacles when designing and interpreting mTBI biomarker studies. To realise the potential of prognostic biomarkers, future research should prioritise establishing consensus definitions, compiling a set of accessible and comprehensive outcome measures, and capturing injury-independent factors through longitudinal study designs.